Current advances in microbial production of 1,3‐propanediol - Zhu, Yueting; Wang, Yanxia; Gao, Hao; Wang, Hanxiao; Wan, Zijian; Jiang, Yujia; Xin, Fengxue; Zhang, Wenming; Jiang, Min (Biofuels, bioproducts and biorefining, 2021)
1,3‐Propanediol (1,3‐PDO), an important chemical raw material, has attracted much attention due to its wide use as a monomer of biodegradable polyester materials. Production of 1,3‐PDO from renewable resources, through microbial fermentation, has the advantage of requiring only mild conditions. The process also demonstrates industrial safety and is environmentally friendly. In this review, we have summarized and commented on current progress in screening and breeding strains for 1,3‐PDO production, especially from glycerol or glucose. Advanced strategies, including metabolic engineering, fermentation process optimization, and construction of a microbial consortium system, are introduced and discussed. Current challenges and prospects for more efficient and economical bio‐based 1,3‐PDO production are examined in the context of its industrial application. © 2021 Society of Chemical Industry and John Wiley & Sons, Ltd